220k views
3 votes
How to factor this polynomial : (x+3)-x(x^2+6x+9)

User Sagi Rika
by
5.2k points

2 Answers

2 votes

Answer:

(x + 3)(- x² - 3x + 1)

Explanation:

Given

(x + 3) - x(x² + 6x + 9) ← factor is a perfect square

= (x + 3) - x(x + 3)² ← factor out (x + 3) from each term

= (x + 3)(1 - x(x + 3))

= (x + 3)(1 - x² - 3x)

= (x + 3)(- x² - 3x + 1)

User KarelG
by
4.6k points
7 votes

Answer:

u will multiply -x by the big bracket and rhen start cancelling and factor it by common numbers

User Planarian
by
4.5k points